2015
DOI: 10.1016/j.cub.2014.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Updating of Visuospatial Memory in Superior Colliculus during Slow Eye Movements

Abstract: Highlights d Visual neurons in monkey SC retain target location during pursuit eye movements d These responses are continuously updated in gaze-centered coordinates d This response is modulated by attention and/or target

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 37 publications
7
63
0
Order By: Relevance
“…Additionally, IOR may be elicited by location more than by object identity (Bichot & Schall, 2002), which seems to be supported by neurophysiological studies. The superior colliculus is critically involved in executing saccades and (disengaging) spatial attention (Dash, Yan, Wang, & Crawford, 2015; Ferreira, Araujo, Matsumoto, Ono, & Nishijo, 2015; Sapir, Soroker, Berger, & Henik, 1999; Wurtz & Goldberg, 1972). As such, activity in the superior colliculus has been shown to reflect IOR (Dorris, Klein, Everling, & Munoz, 2002; Fecteau, Bell, & Munoz, 2004), which is supported by lesion studies showing that IOR is not generated in patients with a lesioned superior colliculus (Sapir et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IOR may be elicited by location more than by object identity (Bichot & Schall, 2002), which seems to be supported by neurophysiological studies. The superior colliculus is critically involved in executing saccades and (disengaging) spatial attention (Dash, Yan, Wang, & Crawford, 2015; Ferreira, Araujo, Matsumoto, Ono, & Nishijo, 2015; Sapir, Soroker, Berger, & Henik, 1999; Wurtz & Goldberg, 1972). As such, activity in the superior colliculus has been shown to reflect IOR (Dorris, Klein, Everling, & Munoz, 2002; Fecteau, Bell, & Munoz, 2004), which is supported by lesion studies showing that IOR is not generated in patients with a lesioned superior colliculus (Sapir et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Dash et al [5] speaks directly to the distinction. Prior to this work, almost all that was known about the neural mechanisms of spatial updating derived from studies employing saccades [14,611], the extremely rapid, highly stereotyped, and discrete eye movements used to sample a visual scene one fixation at a time.…”
Section: Discrete Versus Continuous Updatingmentioning
confidence: 99%
“…In contrast, virtually nothing was known about how the brain updates the representations of remembered visual goals when movements are continuous, as in the case of the smooth pursuit eye movements that would be enlisted to track a fly’s path in space. As described below, by cleverly adapting the key features of a transsaccadic remapping task for use with smooth pursuit eye movements, Dash et al [5] may have revealed a critical neural foundation for this capability.…”
Section: Discrete Versus Continuous Updatingmentioning
confidence: 99%
See 2 more Smart Citations